2021
DOI: 10.1021/acs.jchemed.1c00167
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Procedure When Solving Problem Tasks Based on the Periodic Table: An Eye-Tracking Study

Abstract: This work is focused on upper-secondary school students' ability to use the periodic table of elements to solve problem tasks. Eye-tracking and retrospective think-aloud methods were used to evaluate the reasoning behind the students' (N = 8) performance, i.e., to map the strategies they used and problems they faced when solving the tasks. The data from the eye-tracker were submitted to a quantitative analysis−time fixation duration evaluation on predefined areas of interest. The think-aloud method supporting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 48 publications
3
14
0
1
Order By: Relevance
“…The data were analyzed with the use of IMB SPSS completed with the retrospective-think aloud recordings, as well as interviews. Both were recorded, transcribed verbatim and coded using the set of codes for students' strategies taken from previous studies (Rusek et al, 2019;Tóthová et al, 2021). They were then divided according to Ogilvie (2009)-expansive and limiting.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The data were analyzed with the use of IMB SPSS completed with the retrospective-think aloud recordings, as well as interviews. Both were recorded, transcribed verbatim and coded using the set of codes for students' strategies taken from previous studies (Rusek et al, 2019;Tóthová et al, 2021). They were then divided according to Ogilvie (2009)-expansive and limiting.…”
Section: Discussionmentioning
confidence: 99%
“…Their results showed that the differences lied in the successful solvers' focus on relevant factors, whereas the unsuccessful showed a higher frequency of observing irrelevant factors. In a similarly targeted study, (Tóthová et al, 2021) identified the reasons for unsuccessful problem-solving in chemistry on an example of their periodic table use. Apart from focusing on irrelevant factors, the use of limiting strategies and problems with reading was identified as the main problems.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Havanki and VandenPlas (2014) introduced eye-tracking technology into chemistry education research formally and regarded it as a useful and valuable tool for interpreting results more scientifically, more and more studies have chosen to use this visual survey tool in recent years, but there are still few studies related to the field of video teaching. With the help of eye-tracking technology, chemistry education researchers can explore learners' visual attention and cognitive processes while completing different tasks (Karch et al, 2019;Tang and Pienta, 2022), problem-solving methods and strategies (Tothova et al, 2021;VandenPlas et al, 2021), confirmation of setup demonstration principles (Nehring and Busch, 2020), understanding of chemical phenomena (Hansen et al, 2019), perceptual navigation patterns (Pande and Chandrasekharan, 2022) and some other aspects.…”
Section: Eye-tracking Technology In Chemistry Educationmentioning
confidence: 99%
“…Research showed that pupils have significant gaps in this area. 12 With the obstacle constituted by the difficulty of chemistry concepts and the need to select only the most important, 13 supportive formulas to work with the commonly used rules were also suggested. 14 Secondly, students' results can be affected by the tasks' context which is carried by text.…”
Section: Rusek Et Almentioning
confidence: 99%